Effect of corrosion rate and hardness of titanium in Kokubo’s simulated body fluid for orthodontic applications - Sanny Ardhy Sanny; Islahuddin Islahuddin; Meiki Eru Putra Meiki; Muhammad Riza Ardiyanto riza (BKS-TM Indonesia, 2025)
Titanium and its alloys are widely recognized as preferred materials for dental implants, particularly in orthodontic applications, owing to their superior corrosion resistance and mechanical performance compared with stainless steel. However, certain limitations remain. In acidic environments, titanium’s corrosion resistance tends to decline. This issue is of particular relevance in West Sumatra, where local dietary habits include frequent consumption of acidic and high-fat foods such as rendang, gulai and various fried dishes. Hence, it is important to evaluate the corrosion behavior of titanium and its alloys under acidic conditions. In this study, four titanium-based materials were investigated: Ti-12 Cr, TNTZ-ST, Ti-64 ELI (Extra Low Interstitial), and Commercially Pure Titanium (CpTi). Immersion tests were performed in Kokubo’s Simulated Body Fluid (SBF) at pH 5.0 for four exposure periods (1, 2, 3, and 4 weeks). The corrosion rate was determined using the weight loss method. Results revealed that CpTi exhibited the highest corrosion rate (0.0985 mm/y) after 4 weeks, while Ti-12 Cr demonstrated the lowest (0.0515 mm/y). Regarding hardness, CpTi reached the highest value (365 HVN at 1 week), whereas Ti-12 Cr recorded the lowest (130 HVN).